Womanhood bound to motherhood: Choosing childlessness in Türkiye - Ayşegül Aracı İyiaydın; Ayça Ergun (BMC Psychology, 2025)
Abstract This article aims to evaluate the subjective experiences of voluntarily childless Turkish women, and based on the data collected through in-depth interviews where [a] what it means for them to be a childless woman, [b] what the motivations behind choosing a childless life are, and [c] how they negotiate their childless identity in a pronatalist society are explored. A total of 18 women were interviewed, and three meta-themes [negotiating identity and agency in a pronatalist society, the emotional landscape of childlessness, pathways and motivations for remaining childless] were generated through main themes and subthemes based on the data. All participating women reported some degree of emotional and social distress arising from the stigma they feel within their environmental contexts. Many of them tapped into the “felt outsiderness” among people following traditional gender roles ascribed by Turkish society. All of them felt comfortable with their decision to choose and remain childless despite some difficulties it might bring as a result of living in a society that equates womanhood with motherhood. They presented a variety of individual, familial, and social factors that impact their choice of pursuing a childless life. The article argues that the decision to remain childless is not merely a personal preference but a complex, multi-layered process shaped by sociocultural expectations, gender norms, and individual agency. It highlights how voluntarily childless women actively negotiate their identities within a pronatalist society, challenge traditional narratives surrounding womanhood, and construct meaningful lives that do not conform to dominant reproductive expectations.